Calystegines are Potential Urine Biomarkers for Dietary Exposure to Potato Products. Issue 20 (29th September 2020) - Beckmann, Manfred; Lloyd, Amanda J.; Wilson, Thomas; Torres, Duarte P. M.; Goios, Ana C. L.; Willis, Naomi D.; Lyons, Laura; Phillips, Helen; Mathers, John C.; Nash, Robert J.; Sharp, Hazel; Draper, John
Abstract : Scope: Metabolites derived from specific foods present in urine samples can provide objective biomarkers of food intake (BFIs). This study investigated the possibility that calystegines (a class of iminosugars) may provide BIFs for potato ( Solanum tuberosum L.) product exposure. Methods and results: Calystegine content is examined in published data covering a wide range of potato cultivars. Rapid methods are developed for the quantification of calystegines in cooked potato products and human urine using triple quadrupole mass spectrometry. The potential of calystegines as BFIs for potato consumption is assessed in a controlled food intervention study in the United Kingdom and validated in an epidemiological study in Portugal. Calystegine concentrations are reproducibly above the quantification limit in first morning void urines the day after potato consumption, showing a good dose‐response relationship, particularly for calystegine A3 . The design of the controlled intervention mimicks exposure to a typical UK diet and showed that neither differences in preparation/cooking method or influence of other foods in the diet has significant impact on biomarker performance. Calystegine biomarkers also perform well in the independent validation study. Conclusion: It is concluded that calystegines have many of the characteristics needed to be considered as specific BFIs for potato product intake. Abstract : Calystegines (a class of iminosugars) concentration shows a good dose‐response relationship in first morning void urines the day after potato consumption in intervention and population studies.